2007
DOI: 10.1016/j.molcel.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

MDM2-Regulated Degradation of HIPK2 Prevents p53Ser46 Phosphorylation and DNA Damage-Induced Apoptosis

Abstract: In response to DNA damage, p53 induces either cell-cycle arrest or apoptosis by differential transcription of several target genes and through transcription-independent apoptotic functions. p53 phosphorylation at Ser46 by HIPK2 is one determinant of the outcome because it takes place only upon severe, nonrepairable DNA damage that irreversibly drives cells to apoptosis. Here, we show that p53 represses its proapoptotic activator HIPK2 via MDM2-mediated degradation, whereas a degradation-resistant HIPK2 mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
173
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(188 citation statements)
references
References 44 publications
13
173
0
2
Order By: Relevance
“…As for WSB-1 and Siah-2, Siah-1 depletion by siRNA partially inhibits hypoxia-induced HIPK2 degradation (Moehlenbrink et al, 2010). Interestingly, the p53-inducible Siah-1L protein downregulates HIPK2, suggesting an autoregulatory control of p53 response during hypoxia (Calzado et al, 2009b) similarly to that observed in MDM2 induction after nonsevere DNA damage (Rinaldo et al, 2007b) (Figure 5). In agreement, hypoxic condition by either low oxygen or chemical compound that mimics hypoxia (that is, cobalt chloride) induces p53-target MDM2 that promotes HIPK2 degradation.…”
Section: Hipk2 Inactivation In Tumors and P53 Dysfunctionmentioning
confidence: 65%
See 2 more Smart Citations
“…As for WSB-1 and Siah-2, Siah-1 depletion by siRNA partially inhibits hypoxia-induced HIPK2 degradation (Moehlenbrink et al, 2010). Interestingly, the p53-inducible Siah-1L protein downregulates HIPK2, suggesting an autoregulatory control of p53 response during hypoxia (Calzado et al, 2009b) similarly to that observed in MDM2 induction after nonsevere DNA damage (Rinaldo et al, 2007b) (Figure 5). In agreement, hypoxic condition by either low oxygen or chemical compound that mimics hypoxia (that is, cobalt chloride) induces p53-target MDM2 that promotes HIPK2 degradation.…”
Section: Hipk2 Inactivation In Tumors and P53 Dysfunctionmentioning
confidence: 65%
“…In response to nonsevere DNA damage, HIPK2 is required for PCAF-mediated acetylation of p53 at Lys320 and for p53-induced transcription of the cell cycle inhibitor p21 Waf1 (Di Stefano et al, 2005b). As nonsevere DNA damage also induces MDM2 for HIPK2 proteasomal degradation (Rinaldo et al, 2007b), altogether these findings suggest that different degree of DNA damage can activate HIPK2 and subsequently induce p53 posttranslational modifications to fine-tune p53 transcriptional activity and control cell life or death.…”
Section: Role Of Hipk2 In P53 Acetylationmentioning
confidence: 87%
See 1 more Smart Citation
“…The region of HIPK2 that interacts with ZBTB4 contains the PEST domain, the adjacent autoinhibitory region (Rui et al, 2004) and a destabilization motif (Rinaldo et al, 2007a). This finding has four consequences: First, this portion of HIPK2 also interacts with other proteins, including p53 (Rinaldo et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…In unstressed cells, HIPK2 is complexed with and degraded by Siah-1, whereas in lethally DNAdamaged cells, Siah-1 becomes phosphorylated by ATM/ATR and dissociates from HIPK2 (Winter et al, 2008). In the case of Mdm2, it is increased in sublethally damaged cells due to p53 activation and degrades HIPK2; in lethally damaged cells, Mdm2 protein is present at much lower levels, such that HIPK2 remains stable (Rinaldo et al, 2007). Of note, it has also been reported that HIPK2 may cause apoptosis in a p53-independent manner through downregulating the transcriptional co-repressor CtBP (Zhang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%